Модуль вимірювання крутного моменту при випробуваннях ДВЗ - Глобчак, Михайло; Клипко, Олег; Коцюмбас, Олег (КІНПАТРІ ЛТД, 2013)
The module of measuring of twisting moment is described at research of working process of engine internal combustion on a stand. The electric chart of the module is resulted and a measuring error is appraised.
Module of measuring of twisting moment at the tests of engines internal combustion